2019
DOI: 10.3390/nano9111616
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate Metal Oxide Top Electrode Interface Modification Improves the Thermal Stability of Inverted Perovskite Photovoltaics

Abstract: Solution processed γ-Fe2O3 nanoparticles via the solvothermal colloidal synthesis in conjunction with ligand-exchange method are used for interface modification of the top electrode in inverted perovskite solar cells. In comparison to more conventional top electrodes such as PC(70)BM/Al and PC(70)BM/AZO/Al, we show that incorporation of a γ-Fe2O3 provides an alternative solution processed top electrode (PC(70)BM/γ-Fe2O3/Al) that not only results in comparable power conversion efficiencies but also improved the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Such incorporation improved the power conversion efficiency, thermal stability and charge transport abilities. 81 CaTiO 3 thin layer was incorporated between the perovskite layer and the ETL by Li and his group. Enhanced photovoltaic performance, PCE of 19.12% and better stability even after exposing to ambient air for 1000 hours.…”
Section: Interface Modification Of Perovskite Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such incorporation improved the power conversion efficiency, thermal stability and charge transport abilities. 81 CaTiO 3 thin layer was incorporated between the perovskite layer and the ETL by Li and his group. Enhanced photovoltaic performance, PCE of 19.12% and better stability even after exposing to ambient air for 1000 hours.…”
Section: Interface Modification Of Perovskite Devicesmentioning
confidence: 99%
“…Papadas et al showed that processing γ‐Fe 2 O 3 nanoparticles by solvothermal colloidal synthesis helps to modify the interface of the top electrode in inverted PSCs. Such incorporation improved the power conversion efficiency, thermal stability and charge transport abilities 81 . CaTiO 3 thin layer was incorporated between the perovskite layer and the ETL by Li and his group.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…MeOx are typically used as functional layers in solar cells such as transparent conducting front electrodes (ITO, FTO), ( Kim et al, 1999 ; Han et al, 2007 ) electron (TiO 2 , SnO 2 , ZnO, Fe 2 O 3 etc.) ( Seo et al, 2018 ; Xiong et al, 2018 ; Shin et al, 2019 ; Papadas et al, 2019 ) or hole (Cu:NiOx, CuGaO 2 , NiCo 2 O 4 , CuLi:NiCo 2 O 4 etc.) transporting layers, ( Galatopoulos et al, 2017 ; Papadas et al, 2018a ; Papadas et al, 2018b ; Ioakeimidis et al, 2019 ) whereas a very small number of MeOx have been used as photoactive layers, primarily Cu 2 O, CuO and Co 2 O 3 ( Pérez-Tomás et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that by incorporating a thin Cr layer between the HTL and PSK active layer, diffusion of Au from the metal electrode into the active layer can be reduced [ 18 ]. In our most recent work, we also showed that a top electrode using γ-Fe 2 O 3 (PC 70 BM/γ-Fe 2 O 3 /Al) improved the properties and stability of inverted PSCs under accelerated heat conditions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%